Solar PV powered BLDC motor drive for water pumping using Cuk converter. Issue 2 (1st February 2017) - Kumar, Rajan; Singh, Bhim
Abstract : A solar photovoltaic (SPV) powered brushless DC (BLDC) motor drive for water pumping is presented in this study. The current sensors of BLDC motor and the voltage sensor at the DC bus of voltage‐source inverter (VSI) are eliminated completely. Instead, the speed is controlled by adjusting the DC bus voltage of VSI. The fundamental frequency switching pulses are generated to operate the VSI in order to minimise the switching losses and to enhance the efficiency of proposed system. A DC–DC Cuk converter is utilised to operate the SPV array at its maximum power. The starting current of BLDC motor is bounded by an optimal initialisation and selection of the control parameters, perturbation size and frequency while tracking the peak power of SPV array. The performance of proposed BLDC motor drive is thoroughly evaluated and its potential is demonstrated under realistic operating conditions. The simulated results and an experimental validation along with a comprehensive comparison with the existing techniques demonstrate prominence of the proposed drive for SPV‐based water pumping.